Factors of difficulties in learning the Arabic language for students - Munawarah, Rabiatul; Ilmiani, Aulia Mustika (Institut Agama ISlam Negeri Palangka Raya, 2024)
Different types of difficulties that arise in the learning process result from different factors faced by students and teachers in general, Something similar also happens in learning the Arabic language, so this research aims to find out: 1) the causes of difficulties in learning the Arabic language, 2) students